Da cláusula compromissória nos contratos brasileiros - Chaves, Isadora Costa (2010)
This work approaches the arbitration clause analyzing the formal issues required for its elaboration, considering the legal aspects and the importance given to party free will during contract celebration as well as the limits imposed by public order. Therefore, the central goal of this thesis is to emphasize the legal nature of the arbitration clause and the need to respect validity and efficacy requirements. In order to achieve this goal, author shows the increasing use of the arbitration clause as an efficient way for conflict solution. Thus, the nature of contracts and the evolution of arbitration are briefly discussed. Following, author conceptualizes and analyzes the legal nature of the arbitration clause. Then, several theories on the arbitration convention, its concept and applications are explained. The definition, types and validity conditions of the arbitration clause are presented, as well as the limits imposed by the Consumer Protection Code and in work regulations. In addition, controversial issues regarding the arbitration clause are highlighted. Finally, author shows that alternative ways for conflict resolution are being intensively used in the last years and several questions are raised regarding the Arbitration Law. The parties are aware of the possibility of solving conflicts through arbitration, agreed by them through an arbitral convention or a arbitration clause. Of fundamental importance to solve conflicts which may arise during contract celebration and execution and also to better interpret contract clauses, the arbitration clause should be considered as more than only a standard contract clause